Investigating the Attitudes of Teachers to Science Education in the Irish Primary Classroom - Coppinger, Cora (STER, 2019)
This article aims to provide an insight into current attitudes to science education, which has been correlated from a larger research study conducted by the author. It will compare attitudes recorded in past studies to current primary teachers attitudes to science. It also aims to examine factors affecting teacher’s attitudes to science education at primary level.
Journal article.
Keywords: Research Subject Categories::SOCIAL SCIENCES; Teaching; Attitudes; Primary Education; Science Education; STER; STER